2006
DOI: 10.1063/1.2186309
|View full text |Cite
|
Sign up to set email alerts
|

A two-dimensional adsorption kinetic model for thermal hysteresis activity in antifreeze proteins

Abstract: Antifreeze proteins ͑AFPs͒ and antifreeze glycoproteins ͑AFGPs͒, collectively abbreviated as AF͑G͒Ps, are synthesized by various organisms to enable their cells to survive in subzero environments. Although the AF͑G͒Ps are markedly diverse in structure, they all function by adsorbing to the surface of embryonic ice crystals to inhibit their growth. This adsorption results in a freezing temperature depression without an appreciable change in the melting temperature. The difference between the melting and freezin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
28
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 51 publications
3
28
0
Order By: Relevance
“…Several theoretical studies explained the experimentally observed concentration dependence of the FH activity by assuming that the adsorption of AFPs is reversible (11,(15)(16)(17). To investigate the binding kinetics at the ice-water interface and the dependence of FH on AFP concentration, it is important to understand the respective roles of AFPs in solution and AFPs bound to the ice surface.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several theoretical studies explained the experimentally observed concentration dependence of the FH activity by assuming that the adsorption of AFPs is reversible (11,(15)(16)(17). To investigate the binding kinetics at the ice-water interface and the dependence of FH on AFP concentration, it is important to understand the respective roles of AFPs in solution and AFPs bound to the ice surface.…”
Section: Discussionmentioning
confidence: 99%
“…This theory has been criticized for assuming that the ice-water interface is sharp, contrary to the experimental evidence that the transitions from an ordered solid phase to a liquid phase at the ice-water interfaces are gradual and occur over several layers of water molecules (9-12). Perhaps the hardest criticism to answer is related to the experimentally observed dependence of FH activity on AFP concentration, which strongly suggests a dynamic exchange between adsorbed AFPs and free AFPs in the surrounding solution (11,(13)(14)(15)(16)(17)(18).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…86,103,104 An insightful study by Kristiansen and Zachariassen builds upon the original adsorption-inhibition model, but argues that it is a pressure build-up due to convex ice growth that underlies the Gibbs-Thomson effect. 71 Alternative models consider the anisotropic surface energy of ice, 106 reversible adsorption, [107][108][109][110][111] the polymeric nature of IBPs, 112,113 and lowering of the interfacial tension or step energy. 114,115 …”
Section: A Adsorption-inhibition Modelmentioning
confidence: 99%
“…Furthermore, a transition layer about a nanometer thick 14 in which the molecular order gradually increases between bulk liquid water and ice precludes, according to some researchers, the possibility for a simple, direct attachment of protein to ice. 15 Some of these issues have been attended to in kinetic models based either on reversible 16 or irreversible 12 adsorption of AFP molecules to ice, or even a combination of the two. 17 A large number of biochemical, biophysical, and structural studies have been conducted to elucidate the mechanism by which AFPs bind to specific planes of ice.…”
Section: Introductionmentioning
confidence: 99%